Silence speaks out loud: Armed conflict and bovine livestock in Colombia, a historical perspective - Triana Ángel, Natalia; Burkart, Stefan (International Center for Tropical Agriculture, 2020)
The convoluted nexus between bovine livestock and the dynamics of armed confrontation in Colombia is a terrain open for exploration. While a vast array of archival sources suggests a historical, problematic connection between livestock production, land dispossession and rising violence in rural settings, academic narratives remain scarce. While livestock activities have been largely understood as vital cultural and economic practices in Colombia and Latin America and much has been written on the history of the country’s multifaceted civil war, both phenomena appear to be disconnected from scholarly interpretations. By building on both print media archives and scant, yet path breaking secondary sources, we emphasize two salient perspectives on the topic. First, one literature segment that understands large-scale bovine livestock as a driving force of forced migration and dispossession affecting small producers and peasant communities across Colombia. A second, more recent trend recognizes the critical role of bovine livestock as an opportunity for rural development in impoverished regions, highlighting the importance of livestock systems for different agents, including returning peasants, youth, and even former combatants. Drawing from the experience of Central American communities who, also devastated by recent civil wars, have understood the pivotal function of bovine livestock production as an engine for change and improved livelihoods, we propose a third possible interpretation: one that accounts for the convoluted historical connections between wartime dynamics and cattle and dairy production in Colombia, acknowledges its capacity to empower rural communities in post-conflict contexts and deciphers academic silences as testimonies of its own, violent times. By reconciling divergent postures, our goal is to initiate the conversation around difficult, controversial tropes while seeking to provide methodological and theoretical explanations that can further our understanding on the subject.